Results on the Uniqueness of Difference Polynomials With Difference Operator of Entire Functions Sharing Small Function - Chaithra, C. N.; Naveenkumar, S. H.; Rajeshwari, S. (Communications in Mathematics and Applications, 2023)
In this article, we consider difference polynomials with difference operators, weakly weighted sharing, and relaxed weighted sharing, we investigate the uniqueness problem of difference polynomials. We use \(= (Q(f(z))L(Δ_cf))^(k)\) and \(= (Q(g(z))L(Δ_cg))^(k)\). Accordingly, we have proved three uniqueness results, which extends and improves the results due to G. Haldar (Uniqueness of entire functions concerning differential-difference polynomials sharing small functions, arXiv:2103.09889v1 [math.CV], (2021)).